2020
DOI: 10.1037/npe0000132
|View full text |Cite
|
Sign up to set email alerts
|

Neural activities during the evaluation of luxury goods-to-service brand extension: An event-related potentials (ERPs) study.

Abstract: As a marketing strategy, goods-to-service brand extension has been extensively used for luxury brands. However, little is known about the effectiveness of understanding the neural mechanisms during the evaluation of luxury goods-to-service brand extension. In this study, event-related potentials (ERPs) were applied to investigate the cognitive processes during the evaluation of goods-to-service brand extension in the luxury sector. First, participants were presented with 2 sequential text stimuli of the luxury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
6
3
Order By: Relevance
“…However, the LPP was larger when subjects were exposed to a low fit condition in the context of CSR reputation (relative to CA reputation). The result was different from the previous brand extension study by Song et al (2020) , which discovered that high fit conditions between the luxury brand-service pairs could evoke greater arousing affect compared to low fit ones, as reflected by a greater LPP. Previous studies also pronounced that the LPP component is sensitive to moral or pro-social actions ( Yoder and Decety, 2014 ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, the LPP was larger when subjects were exposed to a low fit condition in the context of CSR reputation (relative to CA reputation). The result was different from the previous brand extension study by Song et al (2020) , which discovered that high fit conditions between the luxury brand-service pairs could evoke greater arousing affect compared to low fit ones, as reflected by a greater LPP. Previous studies also pronounced that the LPP component is sensitive to moral or pro-social actions ( Yoder and Decety, 2014 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Yet, for prestige brands, such as luxury brands, it is possible to be confronted with a risk for their CSR disclosures ( Janssen et al, 2013 ). Moreover, researchers have shown that the consumers’ cognitive process of brand extension toward basic and luxury brands is distinct ( Song et al, 2020 ). Future studies should investigate the two types of brand reputation how to influence luxury brand extension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific ERPs have been identified for the processing of faces, words and meaning, surprise, or memory recall. In neuroscience research, ERP constitutes a millisecond-by-millisecond record of neural information processing, which can be associated with particular operations such as sensory encoding, inhibitory responses and updating working memory (Song et al, 2020). Thus it provides a noninvasive means to evaluate brain functioning in patients with cognitive disorders and is of prognostic value in few cases.…”
Section: Discussionmentioning
confidence: 99%